Analysis on the current status of E -Learning in Colombia Education - Simanca H, Fredys A.; Blanco G, Fabián; Carreño H, Pablo E. (IJRDO- Journal of Educational Research, 2017)
E-Learning is defined as one of the uses of Internet to support learning and is characterized becausethere is a physical separation between teacher and student, through which a didactic interaction isdeveloped. The student becomes the center of the formation, the manager of his own knowledge,naturally with the help of his tutor and classmates. The learning process is an autonomous work usingE-Learning tools which integrates synchronous and asynchronous learning same that is expected to bemotivated by a student research process. It is possible to consider that for the actors (tutor, student andcommunity) is a "face-virtual" experience and you can live a self-determining process in the generationof knowledge. However, if the model is enriching, seemingly from every point of view, it is notdisplayed from the same perspective in the academic modality of undergraduate, where restless littledevelopment that have authoring tools in the context of E-Learning. This is the analysis that we seekto address, generating a debate about this subject, in the same way that it is to recognize if there is acontribution or not to the educational model or the subject of this chapter